Effectiveness and safety of the four-step versus six-step milk ladder in children with IgE-mediated cow’s milk protein allergy: protocol for an open-label randomised controlled trial - Andrea Horvath; Katarzyna Grzela; Daria Wiszniewska; Agata Stróżyk; Anna Nowak‐Wegrzyn; Hanna Szajewska (BMJ Open)
Introduction Introducing baked milk into the diet of children with cow’s milk protein allergy (CMPA) has been shown to potentially accelerate the development of tolerance to non-heated milk. However, there is no standardised milk ladder (ML) protocol, and different scientific societies across countries recommend varying versions. This study aims to assess the effectiveness and safety of the four-step ML (4-ML) compared with the six-step ML (6-ML) in children with IgE-mediated CMPA.Methods and analysis We will perform an open-label randomised trial with two parallel arms in two departments of the same academic hospital. A total of 92 children with IgE-mediated CMPA will be allocated in a 1:1 ratio to introduce cow’s milk into their diet according to either 4-ML or 6-ML with a 4-week break period between subsequent steps. Oral food challenge (OFC) with tested products at each subsequent step of the ML will be conducted in hospital settings. The primary outcome will be the percentage of children with tolerance to non-heated cow’s milk proteins defined as no allergic reaction to raw cow’s milk (120–240 mL depending on the age of the patient) during the last OFC; measured at the end of the 12-week observation period for the 4-ML and 20-week observation period for the 6-ML. Secondary outcomes will include the percentage of children with a negative OFC to each ML step; the percentage of children with anaphylaxis (both those who were treated and those who were not treated with epinephrine); the percentage of children with exacerbation of atopic dermatitis; growth; compliance; and quality of life of the caregivers and parents’ anxiety about adverse events during their child’s OFC.Ethics and dissemination The bioethics committee of the Medical University of Warsaw, Poland, approved this protocol (KB/107/2024). The findings will be published in a peer-reviewed journal and submitted to relevant conferences no later than 1 year after data collection.Trial registration number NCT06664918.